Clinical characteristic analysis of immune checkpoint inhibitor-related pituitary adverse events - Yufan ZHENG; Jingjing WANG; Qin YUAN; Fenping ZHENG (Zhongguo Linchuang Yixue)
ObjectiveTo explore the clinical characteristics of immune-related adverse events (irAEs) involving the pituitary gland in malignant tumor patients following the administration of immune checkpoint inhibitors (ICIs), and to compare characteristics of pituitary irAEs with primary hypophysitis. MethodsA total of 753 malignant tumor patients who were hospitalized at Sir Run Run Shaw Hospital School of Medicine, Zhejiang University from January 2019 to November 2022 and received ICIs treatment were retrospectively included. The incidence of endocrine irAEs were statistically analyzed. The clinical characteristics of patients with pituitary irAEs were analyzed and compared with those of patients with primary hypophysitis (n＝18). ResultsAmong the 753 patients treated with ICIs, the majority (742, 98.5%) received PD-1/PD-L1 inhibitors. The incidence of endocrine irAEs was 32.0% (241/753), with primary thyroid dysfunction being most common (212, 28.2%), followed by pituitary dysfunction (35, 4.6%). The median time to onset of pituitary irAEs was 5.8 months, with the majority presenting as secondary hypoadrenocorticism (33, 94.3%). Surgery was a protective factor for preventing pituitary irAEs (P＝0.002), whereas higher body mass index (BMI) and dual ICIs combination therapy were recognized as risk factors (P＜0.05). Compared to patients with primary hypophysitis, patients with pituitary irAEs had a higher proportion of males, lower BMI, lower rates of visual field defects and diabetes insipidus, higher rate of secondary hypoadrenocorticism and lower positive rate on MRI (P＜0.05).ConclusionsMalignant tumor patients treated with ICIs exhibit a relatively high incidence of endocrine irAEs, with thyroid involvement being most common, followed by the pituitary gland. Pituitary irAEs primarily manifest as secondary hypoadrenocorticism, lacking specific clinical symptoms and exhibiting a low positive rate on MRI. These factors contribute to a high risk of misdiagnosis or missed diagnosis, necessitating heightened clinical vigilance.